2016
DOI: 10.1093/hmg/ddw232
|View full text |Cite
|
Sign up to set email alerts
|

The chaperone HSPB8 reduces the accumulation of truncated TDP-43 species in cells and protects against TDP-43-mediated toxicity

Abstract: Aggregation of TAR-DNA-binding protein 43 (TDP-43) and of its fragments TDP-25 and TDP-35 occurs in amyotrophic lateral sclerosis (ALS). TDP-25 and TDP-35 act as seeds for TDP-43 aggregation, altering its function and exerting toxicity. Thus, inhibition of TDP-25 and TDP-35 aggregation and promotion of their degradation may protect against cellular damage. Upregulation of HSPB8 is one possible approach for this purpose, since this chaperone promotes the clearance of an ALS associated fragments of TDP-43 and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 68 publications
4
87
1
Order By: Relevance
“…In particular, the upregulation of the chaperone HSPB8, or of its Drosophila melanogaster homolog (HSP67Bc) was shown to protect against protein aggregation and toxicity in cell and fly models of ALS and polyglutamine diseases and cooperation between HSPB5 and the mammalian disaggregase machinery was very effective in dissolving protein aggregates (Carra et al, 2010; Duennwald et al, 2012; Crippa et al, 2016). Conversely, mutations in small HSPs such as HSPB1, HSPB3, HSPB5, HSPB8 and the co-chaperones DNAJB6 and BAG3 have all been associated with motor neuron and muscular diseases (Vicart et al, 1998; Selcen et al, 2009; Couthouis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the upregulation of the chaperone HSPB8, or of its Drosophila melanogaster homolog (HSP67Bc) was shown to protect against protein aggregation and toxicity in cell and fly models of ALS and polyglutamine diseases and cooperation between HSPB5 and the mammalian disaggregase machinery was very effective in dissolving protein aggregates (Carra et al, 2010; Duennwald et al, 2012; Crippa et al, 2016). Conversely, mutations in small HSPs such as HSPB1, HSPB3, HSPB5, HSPB8 and the co-chaperones DNAJB6 and BAG3 have all been associated with motor neuron and muscular diseases (Vicart et al, 1998; Selcen et al, 2009; Couthouis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One such family of protective factors could be the sHSPs. For example, using a Drosophila model for TDP-43 neurodegeneration, it was shown that overexpression of HSP67Bc (the Drosophila ortholog of HSPB8) rescued the eye degeneration whereas downregulation of HSP67Bc worsened the eye phenotype (Crippa et al 2016a). TDP-35 and TDP-25 are C-terminal fragments obtained after caspase cleavage of full-length TDP-43.…”
Section: Als-tdp-43 (Tardbp)mentioning
confidence: 99%
“…In a Drosophila model overexpressing TDP-35, HSP67Bc rescued pupae lethality (Crippa et al 2016a). Similarly, overexpression of human HSPB8 in neuronal cell models for ALS also protected against aggregation seeding by TDP-25, TDP-35, and TDP-43 (Crippa et al 2010;Crippa et al 2016a;Crippa et al 2016b;Cicardi et al 2018). Moreover, using an elegant approach, FDA/EMAapproved small molecules that upregulate HSPB8 were identified.…”
Section: Als-tdp-43 (Tardbp)mentioning
confidence: 99%
“…It has been suggested that within the multichaperone complex organized by BAG3, HSPB8 provides the substrate recognition capacity. Besides, overexpression of HSPB8 can stimulate the autophagic degradation of many misfolded protein substrates in a BAG3-dependent manner (18,(42)(43)(44). However, BAG3 can function without HSPB8 in the clearance of harmful protein products (18,25).…”
mentioning
confidence: 99%